The Scleraxis Transcription Factor Directly Regulates Multiple Distinct Molecular and Cellular Processes During Early Tendon Cell Differentiation - Liu, Han; Xu, Jingyue; Lan, Yu; Lim, Hee-Woong; Jiang, Rulang (Frontiers in Cell and Developmental Biology, 2021)
Proper development of tendons is crucial for the integration and function of the musculoskeletal system. Currently little is known about the molecular mechanisms controlling tendon development and tendon cell differentiation. The transcription factor Scleraxis (Scx) is expressed throughout tendon development and plays essential roles in both embryonic tendon development and adult tendon healing, but few direct target genes of Scx in tendon development have been reported and genome-wide identification of Scx direct target genes in vivo has been lacking. In this study, we have generated a ScxFlag knockin mouse strain, which produces fully functional endogenous Scx proteins containing a 2xFLAG epitope tag at the carboxy terminus. We mapped the genome-wide Scx binding sites in the developing limb tendon tissues, identifying 12,097 high quality Scx regulatory cis-elements in-around 7,520 genes. Comparative analysis with previously reported embryonic tendon cell RNA-seq data identified 490 candidate Scx direct target genes in early tendon development. Furthermore, we characterized a new Scx gene-knockout mouse line and performed whole transcriptome RNA sequencing analysis of E15.5 forelimb tendon cells from Scx-/- embryos and control littermates, identifying 68 genes whose expression in the developing tendon tissues significantly depended on Scx function. Combined analysis of the ChIP-seq and RNA-seq data yielded 32 direct target genes that required Scx for activation and an additional 17 target genes whose expression was suppressed by Scx during early tendon development. We further analyzed and validated Scx-dependent tendon-specific expression patterns of a subset of the target genes, including Fmod, Kera, Htra3, Ssc5d, Tnmd, and Zfp185, by in situ hybridization and real-time quantitative polymerase chain reaction assays. These results provide novel insights into the molecular mechanisms mediating Scx function in tendon development and homeostasis. The ChIP-seq and RNA-seq data provide a rich resource for aiding design of further studies of the mechanisms regulating tendon cell differentiation and tendon tissue regeneration. The ScxFlag mice provide a valuable new tool for unraveling the molecular mechanisms involving Scx in the protein interaction and gene-regulatory networks underlying many developmental and disease processes.